Analysis of NLR in Type 2 Diabetes Mellitus with and without Diabetic Foot Ulcer - Rafika Ulandari; Liong Boy Kurniawan; Nurahmi Nurahmi; Darwati Muhadi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Patients with type 2 diabetes mellitus (T2DM) have increased followed by complications including diabetic foot ulcer. Systemic inflammatory conditions in T2DM with diabetic foot ulcers can be assessed by inflammatory markers. Neutrophil Lymphocyte Ratio (NLR) is a good indicator of systemic inflammatory conditions. A retrospective study of the medical record at Dr. Wahidin Sudirohusodo Hospital, Makassar from September 2019 – September 2021 involved 120 patients consisting of 60 patients for each group of T2DM with and without diabetic foot ulcers. Leukocytes, neutrophils, lymphocytes, and NLR based on routine blood results using the flow cytometry method. Mann-Whitney test was used for comparison between the two groups on NLR and Kruskal-Wallist test was used for the relationship between NLR and Wagner classification. There was a significant difference in leukocytes, neutrophils, lymphocytes, and NLR in T2DM patients with diabetic foot ulcers compared to those without 16.2±8.6 and 9.8±4.2 103/µL (p<0.001); 13.3±8.4 and 5.0±3.8 103/µL(p<0.001); 1.6±1.7 and 2.5±2.5 103/µL(p<0.001); 10.0±10.1 and 3.5±4.5, respectively. The relationship between the NLR and Wagner classification was the highest at Wagner grade 5 (12.87±5.0) and the lowest was at Wagner grade 2 (6.18±7.83) with significant statistical test results (p<0.037). There was increasing NLR in T2DM with diabetic foot ulcers due to systemic inflammation. The NLR integrates different immune pathways, such as neutrophils as an inflammatory response and lymphocytes controlling the inflammatory response. Lymphocytes count and NLR level on T2DM with diabetic foot ulcer were higher than those without diabetic foot ulcer.